Profesionalisme Keinsinyuran untuk Pengelolaan Persampahan Perkotaan yang Berkelanjutan di Indonesia - Sumarlin, Sumarlin; Sucipto, Sucipto (FAKULTAS TEKNIK UMKENDARI, 2026)
Rapid population growth and massive urbanization in Indonesia have increased municipal solid waste generation while simultaneously placing significant pressure on conventional waste management systems based on final disposal sites. This phenomenon has become increasingly complex due to limited land capacity, environmental pollution impacts, and disparities in governance maturity across regions, which hinder the transition toward Integrated Solid Waste Management (ISWM) based on circular economy principles. This study adopts a community education approach and the dissemination of science and technology to enhance community capacity in sustainable waste management. This approach emphasizes strengthening literacy on sustainability principles, the circular economy, and engineering professionalism through the transfer of innovative waste management technologies. The results indicate that the integration of education and science–technology diffusion is able to improve public understanding, participation, and adaptive capacity. In this context, engineering professionalism plays a strategic role through the application of systems thinking, environmentally friendly technological innovation, and decision-making processes. Synergy among government, communities, and engineers is essential to realizing an efficient, adaptive, and sustainable urban solid waste management system aligned with the Sustainable Development Goals (SDGs). The implications of this study highlight the importance of strengthening collaborative policies and fostering continuous innovation at the urban level.